Bidirectional scan-based velocity scheduling algorithm for proton arc gantry with limited jerk - Zhou, Shiyi; Fan, Qingkun; Qian, Yujia; Dao, Riao; Lu, Xiliang; Yang, Zhijian; Ding, Xuanfeng; Peng, Gang; Zhang, Sheng; Yang, Kunyu; Wang, Ye; Liu, Gang; et al. (Physics in medicine & biology, 2025)
Objective . Spot-scanning proton arc therapy (SPArc) is an innovative planning and delivery framework for proton arc therapy that achieves conformal dose distribution via the rotating gantry. The clinical implementation of SPArc relies on efficient treatment delivery and smooth gantry rotation, with gantry velocity scheduling playing a crucial role in addressing this challenge. This study proposes a bidirectional scan-based gantry velocity scheduling algorithm, designated as BD SPArc , to enhance the delivery efficiency and generate smooth gantry velocity profiles for SPArc plans concerning the mechanical and clinical requirements. Approach . For a given SPArc plan, BD SPArc generates the gantry velocity profile by determining maximum feasible gantry velocities that allow sufficient time for irradiation and energy layer switch based on a bidirectional scan procedure. The profile with limited jerk (time derivative of acceleration) is then used to connect the velocities at the adjacent gantry angles. The SPArc delivery sequence model (DSM SPArc ) was used as a benchmark. SPArc plans for nine clinical cases, including brain, liver, lung, prostate, and head & neck cancers, were utilized for the evaluation. The performance of BD SPArc was evaluated based on the dynamic delivery time, the lost time (the difference between the dynamic delivery time and the fix beam delivery time), and the order of continuity of the gantry velocity profile. Main Results . Compared with DSM SPArc , BD SPArc significantly enhances the delivery efficiency, reducing the average dynamic delivery time from 308.5 ± 10.0 s to 273.1 ± 18.5 s and the lost time from 48.1 ± 10.0 s to 12.6 ± 3.1 s. Meanwhile, it increases the smoothness of the gantry velocity profile. Significance . BD SPArc is a novel gantry velocity scheduling algorithm for SPArc treatment delivery that enhances the delivery efficiency and generates smoother velocity profiles compared with DSM SPArc , offering a practical and optimized ingredient in SPArc planning.